Delayed Venous Repair for Distal Phalanx Replantation - Zamfirescu, Dragos; Salman, Mohammed; Lascar, Ioan (Journal of Reconstructive Microsurgery, 2012)
Background Vein anastomosis is the most important factor determining the success in the replantation of distal phalanx amputations. It is very difficult to find the collapsed veins and to perform vein anastomosis immediately after arterial repair. We have chosen to delay the vein repair between 30 minutes and 1 hour to give time to the veins to expand to a more reasonable diameter for repair.Aim The purpose of the study was to show that the delayed venous method provides a higher rate of success in distal phalanx replantations and does not require the use of specialized techniques.Methods The delayed venous method for vein anastomosis was used for the past 2 years. This surgical procedure includes initial arterial anastomosis, delayed expansion of the vein, and subsequent vein anastomosis after 30 mins of waiting.Results The delayed method was used in eight cases. Expansion of veins up to 1 mm or more resulted in a high success rate (75%). In contrast, the success rate for distal phalanx replantation is extremely low in other techniques because of the difficulty of vein finding and anastomosis.Conclusion The delayed venous method allows easier anastomosis of the subdermal veins of the distal phalanx. Therefore, it is a useful operative technique for treatment of amputated distal phalanx amputation.
Keywords: replantation; distal phalanx; venous anastomosis; delay